The relationship between central obesity and risk of breast cancer: a dose–response meta-analysis of 7,989,315 women - Chen, Hongyang; Yuan, Mengqi; Quan, Xiaomin; Chen, Dongmei; Yang, Jingshu; Zhang, Chenyang; Nan, Yunxin; Luo, Fan; Wan, Donggui; Yang, Guowang; An, Chao (Frontiers in Nutrition, 2023)
Purpose: Central obesity may contribute to breast cancer (BC); however, there is no dose-response relationship. This meta-analysis examined central obesity's effects on BC and their potential dose-response relationship. Methods: In the present study, PubMed, Medline, Embase, and Web of Science were searched on 1 August 2022 for published papers. We included the prospective cohort and case-control studies that reported the relationship between central obesity and BC. Summary effect-size estimates were expressed as Risk ratios (RRs) or Odds ratios (ORs) with 95% confidence intervals (95% CI) and were evaluated using random-effect models. The inconsistency index (I2) was used to quantify the heterogeneity magnitude derived from the random-effects Mantel-Haenszel model Results: This meta-analysis included 57 studies (26 case-control and 31 prospective cohort) as of August 2022. Case-control studies indicated that waist circumference (WC) were significantly positively related to BC. Subgroup analysis showed that central obesity measured by WC increased the premenopausal and postmenopausal BC risk. And the same relationship appeared in WHR during premenopausal and postmenopausal . The same relationship was observed in hormone receptor-positive (HR+) and hormone receptor-negative (HR-) BCs. Prospective cohort studies indicated that high WC and WHR may increase BC risk. Subgroup analysis demonstrated a significant correlation during premenopausal and postmenopausal between BC and central obesity measured by WC, and WHR was significantly positively related to BC both premenopausa and postmenopausal. Regarding molecular subtype, central obesity was significantly associated with HR+ and HR- BCs. Our dose-response analysis revealed a J-shaped trend in the relationship between central obesity and BC (measured by WC and WHR) in case-control studies and an inverted J-shaped trend between BMI (during premenopausal) and BC in prospective cohort. Conclusion: Central obesity is a risk factor for premenopausal and postmenopausal BC, and WC and WHR may predict it. Regarding the BC subtype, central obesity is proven to be a risk of ER+ and ER- BCs. The dose-response analysis revealed that when BMI (during premenopausal) exceeded 23.40 kg/m2，the risk of BC began to decrease, and WC higher than 83.80 cm or WHR exceeded 0.78 could efficiently increase the BC risk.